Consumption of Ultra-Processed Foods by Pesco-Vegetarians, Vegetarians, and Vegans: Associations with Duration and Age at Diet Initiation - Gehring, Joséphine; Touvier, Mathilde; Baudry, Julia; Julia, Chantal; Buscail, Camille; Srour, Bernard; Hercberg, Serge; Péneau, Sandrine; Kesse-Guyot, Emmanuelle; Allès, Benjamin (The Journal of nutrition, 2021)
There is a growing availability of industrial plant-based meat and dairy substitutes that can be classified as ultra-processed foods (UPFs). Very little is known about the consumption of UPFs by vegetarians. The aim of this cross-sectional study, from the NutriNet-Santé cohort, was to describe the contribution of UPFs to different vegetarian diets, in relation to the nutritional quality of their diet, and determinants of UPF consumption, including duration and age at vegetarian diet initiation. The study population (n = 21,212) was divided into 4 groups: 19,812 meat eaters, 646 pesco-vegetarians, 500 vegetarians, and 254 vegans. Daily food intakes were collected using repeated 24-h dietary records. Vegetarian diets were described by the proportion of energy from UPFs and the nutritional quality of the diet using healthy and unhealthy plant-based diet indices (PDIs). In a subsample without meat eaters (n = 1,400), a multivariable linear regression model was performed to study the association between UPF consumption and its determinants. Higher avoidance of animal-based foods was associated with a higher consumption of UPFs (P < 0.001), with UPFs supplying 33.0%, 32.5%, 37.0%, and 39.5% of energy intakes for meat eaters, pesco-vegetarians, vegetarians, and vegans. The nutritional quality of diets was also associated with the level of animal-based foods avoidance (P < 0.001), with healthy PDIs at 53.5, 60.6, 61.3 and 67.9 for meat-eaters, pesco-vegetarians, vegetarians, and vegans. Short duration and young age at diet initiation were associated with an increased consumption of UPFs (βage at initiation = -0.003, P = 0.001; βduration = -0.002, P < 0.001). Not all vegetarian diets necessarily have health benefits, because of potential adverse effects of UPFs on nutritional quality and healthiness of diet. UPF consumption by vegetarians and their diet characteristics should be considered in future studies on the links between vegetarianism and health. This trial was registered at clinicaltrials.gov as NCT03335644.